2023
DOI: 10.1038/s41598-023-39591-8
|View full text |Cite
|
Sign up to set email alerts
|

Clustering-based spatial analysis (CluSA) framework through graph neural network for chronic kidney disease prediction using histopathology images

Abstract: Machine learning applied to digital pathology has been increasingly used to assess kidney function and diagnose the underlying cause of chronic kidney disease (CKD). We developed a novel computational framework, clustering-based spatial analysis (CluSA), that leverages unsupervised learning to learn spatial relationships between local visual patterns in kidney tissue. This framework minimizes the need for time-consuming and impractical expert annotations. 107,471 histopathology images obtained from 172 biopsy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The remaining question is which concept is proven in a proof-of-concept trial based on histological constructs without any meaning. Recent studies making use of unsupervised machine learning have identified tissue areas that have no names in traditional kidney pathology, 6,7 but very little effort was made to understand them, questioning whether the new ideas and hypotheses that AI brings will be used for scientific interest or just taken for granted.…”
mentioning
confidence: 99%
“…The remaining question is which concept is proven in a proof-of-concept trial based on histological constructs without any meaning. Recent studies making use of unsupervised machine learning have identified tissue areas that have no names in traditional kidney pathology, 6,7 but very little effort was made to understand them, questioning whether the new ideas and hypotheses that AI brings will be used for scientific interest or just taken for granted.…”
mentioning
confidence: 99%